Characteristics determination for milling working equipment of excavator - I. S. Kuznetsov; S. V. Saveliev (Вестник СибАДИ)
Introduction. The long network of pipelines on the territory of our country needs timely and high-quality repairs. The entrenching tool used so far increases the complexity of work on the overhaul of pipelines, which forces to create solutions for mechanizing the process of digging the pipeline. The purpose of the study conducted in this article is to determine the performance and total torque of the working equipment of the excavator. A general view of the working equipment with the designation of the positions necessary for the study is given. Methods and materials. The concept of specific values of torque and power per one cutter of working equipment has been introduced. The dependencies of the total productivity of the cutters and the torque of the cutters are established. Due to the peculiarity of the design of the working equipment, each of the dependencies is considered separately for the front and rear incisors. The surfaces that reflect the influence of the angular velocity of rotation of the milling head and the angle of installation of the cutters on the parameters under the study are constructed. Results. Based on the obtained dependence of the total torque of the milling working equipment, a nomogram was compiled. By setting the number of N cutters, the speed of rotation of n working milling head and the number of strokes of the DorNII (Road Research Institute) striker, it is possible to determine the required torque of the hydraulic motor. Сonclusions. According to the results of the theoretical study of the process of cutting soil with the help of excavator milling working equipment, the dependencies of the total productivity and total torque of the working equipment were established. The constructed graphic dependencies help to determine the degree of influence of design and operating parameters on the work process. The created nomogram is recommended for use in the design of working equipment.